3x+11=60-40

Simple and best practice solution for 3x+11=60-40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+11=60-40 equation:


Simplifying
3x + 11 = 60 + -40

Reorder the terms:
11 + 3x = 60 + -40

Combine like terms: 60 + -40 = 20
11 + 3x = 20

Solving
11 + 3x = 20

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + 3x = 20 + -11

Combine like terms: 11 + -11 = 0
0 + 3x = 20 + -11
3x = 20 + -11

Combine like terms: 20 + -11 = 9
3x = 9

Divide each side by '3'.
x = 3

Simplifying
x = 3

See similar equations:

| 9x^2+9y^2=135 | | 5x*(x+7)-5=0 | | 2x^2+23x+30=154 | | 2x^2+23x=154 | | 2x^2+23x=124 | | x^2-5x-2.75=0 | | 12x-42=5x+14 | | Y^4-12y^2+32=0 | | f(x)=2x^2-8x+5 | | x^2+16x-41=0 | | -24=y/4 | | g/5=-13 | | 3/x+4x/x-3=4 | | 9x+14=(x-13) | | p+2p=3 | | x^2+8-1=19 | | ((t^2-9)/(t+3))*(4/16t) | | 3(4c-1)-5=8c+8 | | 7x-49y=14 | | 16=2(q+4)+3 | | 3a^2+18a-7=0 | | 3a^2+6a-7=0 | | 0.5n+(-0.25)+0.075n=0.5+(-0.025n) | | 3/8=x/56 | | 100=10e^2t | | 0.5n+(-0.25)+0.075n=0.5(-0.025n) | | 0.5n+(-0.25)+0.075n=0.5(-0.025) | | (5x+15)(5x+15)=200 | | 25x^2+75x+225=200 | | 6x+(-5)=2x+(-3) | | 2(x^2-x-110)=0 | | 7x+-2x+x=42 |

Equations solver categories